Evaluation of fatigue in patients with pancreatic cancer receiving chemotherapy treatment: a cross-sectional observational study - Di Marco, Mariacristina; Rubbi, Ivan; Baldi, Agnese; Di Lorenzo, Rosaria; Magnani, Daniela; Cremonini, Valeria; Sarli, Leopoldo; Artioli, Giovanna; Ferri, Paola (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Cancer-related fatigue (CRF) is one of the most common symptoms experienced by cancer patients (CPs) and negatively affects quality of life. Although CRF is frequently experienced, it is often underreported, underdiagnosed and undertreated. The objectives of this study were to evaluate the level of fatigue in patients with pancreatic cancer undergoing chemotherapy and to analyse its correlation with patients’ demographic and clinical variables. Methods: A cross-sectional observational study was implemented in the Oncology Day Hospital of a Northern Italian hospital. A sample of 48 patients receiving chemotherapy were evaluated through the Brief Fatigue Inventory Italian version (BFI-I) between 1 May and 12 October 2016. Data were statistically analysed. Results: Most of our patients (94%) experienced fatigue. Women as well as patients with an age ≥65 years reported more fatigue. Anemia, pain and a weight loss of over 16 kg in the last 6 months were significantly related to the perception of fatigue. Regarding life habits, smoking was related to high global score of BFI-I. Conclusions: In accordance with literature, our study suggests that fatigue is a frequent symptom influenced by many constitutional, clinical and environmental factors. Our results highlight the need for an early and regular evaluation of fatigue among cancer patients, in order to implement all those pharmacological and non-pharmacological interventions with proven efficacy in attenuating this symptom.